2020
DOI: 10.3390/bios10100144
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Experimental and Theoretical Studies on an Electrochemical Immunosensor

Abstract: Electrochemical immunosensors (EIs) integrate biorecognition molecules (e.g., antibodies) with redox enzymes (e.g., horseradish peroxidase) to combine the advantages of immunoassays (high sensitivity and selectivity) with those of electrochemical biosensors (quantitative electrical signal). However, the complex network of mass-transfer, catalysis, and electrochemical reaction steps that produce the electrical signal makes the design and optimization of EI systems challenging. This paper presents an integrated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 67 publications
(78 reference statements)
0
5
0
Order By: Relevance
“…The successful application of our integrated experimental and modeling framework in this paper for IBE biosensors and in a previous paper for a novel amperometric electrochemical immunosensor [26] has demonstrated that the approach is generic and has wide utility for mechanistic modeling of the key mass-transfer and reaction steps that determine the biosensor's amplitude and sensitivity. Moreover, the novel dimensional-analysis approach (e.g., current-control coefficients, sensitivity coefficients, and Damkohler numbers) has been shown to be capable of determining the degree to which various steps limit the biosensor's signal magnitude and sensitivity to the target analyte.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…The successful application of our integrated experimental and modeling framework in this paper for IBE biosensors and in a previous paper for a novel amperometric electrochemical immunosensor [26] has demonstrated that the approach is generic and has wide utility for mechanistic modeling of the key mass-transfer and reaction steps that determine the biosensor's amplitude and sensitivity. Moreover, the novel dimensional-analysis approach (e.g., current-control coefficients, sensitivity coefficients, and Damkohler numbers) has been shown to be capable of determining the degree to which various steps limit the biosensor's signal magnitude and sensitivity to the target analyte.…”
Section: Discussionmentioning
confidence: 89%
“…We recently developed a novel, integrated experimental and modeling framework that includes a steady-state, mechanistic mathematical model that describes the rate of key mass-transfer and reaction steps and a novel dimensional-analysis approach to assess the degree to which individual mass-transfer and reaction steps limit the biosensor's amplitude and sensitivity [26]. We then demonstrated the framework's utility using a novel amperometric electrochemical immunosensor.…”
Section: Introductionmentioning
confidence: 99%
“…The immobilization of the antibody on the SAM layer was performed using EDC/NHS coupling, forming a covalent bond between the carboxylic acid and a primary amine, as previously described [24,28,29]. The electrodes were exposed to a fresh 1:2 solution of NHS and EDC in a 50 mM MES buffer at pH 5.0 for 40 min and subsequently rinsed.…”
Section: Antibody Immobilizationmentioning
confidence: 99%
“…The chronoamperometric detection method can be used in combination with immunosandwich complexes to render the electrochemical signal dependent on an antigen concentration, as demonstrated in [29,[48][49][50][51]. A standard practice for biosensors is to amplify the signal as a means of increasing the sensitivity.…”
Section: Electrochemical Signal Amplification Strategymentioning
confidence: 99%
“…There are numerous ways of applying theory to biosensing, and we can classify them into continuous or large-scale modeling and molecular modeling. On the one hand, continuous modeling is habitually used to propose semi-empirical equations to describe some specific property and then solve them for a given set of parameters [154]. After that, the obtained characteristic curve can be compared to the experimental result.…”
Section: Theory and Simulation Of Biosensingmentioning
confidence: 99%